Aesthetic of naming: Potential psycho-sociological effects of some forenames in use among Zimbabweans - Manyarara, Barbra C.; Gora, Ruth B. (Journal for Studies in Humanities and Social Sciences, 2015)
Naming aesthetics in Zimbabwe as in the rest of African cosmology have always been incident-based and this trend somewhat persists. The aesthetic of naming is a parent or guardian’s prerogative and expresses that individual/s wishes, joys, fears and attitudes but may not necessarily consider the named’s future perceptions or feelings engendered by the particular name that identifies them. Various studies have established general naming practices in Zimbabwe and off er many reasons to account for name types. For example, some Shona names are thought repositories of human experience while others are regarded as argument by proxy. Whereas most previous studies on onomastic practices in Zimbabwe have tended to focus on name etymologies and name meanings, the present paper seeks to assess the potential psycho-sociological effects of some significantly negative forenames encountered in school registers and on university graduation lists. A name may not have much statistical significance but when anyone human being carries it, the name becomes sufficiently important as is illustrated in the present discussion on the potential effects of just two common Zimbabwean names, ‘Mistake and Murambiwa’.